Optimizing Sustainable, Affordable and Healthy Diets and Estimating the Impact of Plant-Based Substitutes to Milk and Meat: A Case Study in Spain - Abejon-Elias, R (Elsevier Ltd, 2023)
The global food system is failing to appropriately nourish the population and has been identified as a driving force for environmental degradation. Changing current diets to healthier and more sustainable ones is key to decrease the incidence of non-communicable diseases and force changes at the production stage that will release environmental pressure. The determination of such diets is a challenge since it should be context specific, culturally acceptable, affordable, nutritionally adequate, and environmentally friendly. Through multiobjective optimization we aimed to determine a sustainable and healthy diet(SHD) in Spain with the minimum cost and environmental impact (assessed through GHGe, land use and blue-water use) that deviate the least from current consumption. Additionally, this research also compares the optimised diet with the Spanish food-based dietary guidelines(FBDG), and explores the potential benefits of reducing animal meat and milk while replacing them with plant-based alternatives. Compared to current consumption, a SHD in Spain can be more nutritious and reduce cost, GHGe, land and blue-water use by 32%, 46%, 27%, and 41%, respectively. The Spanish intake displayed the worst nutritional assessment and the highest values for GHGe and land use. The Spanish FBDG showed the highest cost and blue-water usage. Further analysis revealed that plant-based meat alternatives are not necessary to achieve a nutritionally adequate diet at the minimum cost and environmental impact. Shifting to fortified plant-based milk alternatives may add additional environmental benefits. This work emphasizes the potentiality of using optimization to determine a SHD and identifies important gaps to be fulfilled in future research. © 2023 Elsevier Ltd